Medical Corruption: Causes and Measures of Combating - Bondarenko, Olha S.; Utkina, Maryna S (Green Publisher Indonesia, 2023)
After the Ukrainian crisis, many renewal processes took place in Ukraine. One of the most important reforms was anti-corruption. The issue of medical corruption has gotten worse in the context of the global pandemic caused by Сovid-19. Methodology is a conjunction of approaches, principles, and specific methods, which are used by the scientist. We used exactly those elements of the methodology that allowed us to ensure the consistency and objectivity of the combating corruption in the medical field in Ukraine study. The authors outline and characterize the main causes of medical corruption in Ukraine. Measures to combat medical corruption are proposed as follows: modernization of the model of medical field financing; commissioning of a special procedure for purchasing pharmaceuticals at public expense; overcoming the corruption component in the cooperation of pharmaceutical companies and medical workers; reforming the remuneration system of medical workers; educational activities.